2006
DOI: 10.1620/tjem.210.91
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Patency Rates and Complications of Upper Extremity Arteriovenous Fistulae Created for Hemodialysis

Abstract: ATES, A., ÖZYAZICIOĞLU, A., YEKELER, I., CEVIZ, M., ERKUT, B., KARAPOLAT, S., KOÇOĞULLARI, C.U. The types of fistulae used and their complication rates are important for the hemodialysis patients. We aimed to compare retrospectively the primary and secondary patency rates and complications of upper extremity arteriovenous fistulae. Between 1984 and 2005, a total of 1,233 upper extremity arteriovenous fistulae were created in 920 patients. The mean age was 42 ± 21 years. The fistulae were divided into the 3 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Recent studies have also found that when thrombosed, grafts are more successfully treated with radiologic intervention with a 63% 6-mo postinterventional patency rate compared with 22% in AVF (79,80). Some studies have also shown superior graft primary and secondary patency compared with AVF (33,81), especially when it is a second access (72). Indeed, with multidisciplinary care, graft survival has progressively improved in the past decade and can exceed K/DOQI recommended patency rates (82).…”
Section: Impact On the Patient: The Patient Is Firstmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also found that when thrombosed, grafts are more successfully treated with radiologic intervention with a 63% 6-mo postinterventional patency rate compared with 22% in AVF (79,80). Some studies have also shown superior graft primary and secondary patency compared with AVF (33,81), especially when it is a second access (72). Indeed, with multidisciplinary care, graft survival has progressively improved in the past decade and can exceed K/DOQI recommended patency rates (82).…”
Section: Impact On the Patient: The Patient Is Firstmentioning
confidence: 99%
“…They have been found to have higher rates of complications such as aneurysms (81,84,85) and have a significantly greater risk for infection compared with AVF (71). Historically, they have required more interventions to manage stenosis and thrombosis (71); however, with the introduction of the CPM indicator of structured routine monitoring and intervention, thrombosis rates are now low (86,87).…”
Section: Impact On the Patient: The Patient Is Firstmentioning
confidence: 99%
“…Se kon der açık ka lım üst eks tre mi te prok si mal seg ment ler de oluş tu ru lan AVF 'de da ha ba şa rı lı ol du ğu bil di ril miş tir. 13,14 Ça lış -ma mız da bu bul gu lar la uyum lu dur ve se kon der açık ka lım her iki grup ta da yük sek sey ret miş tir. Se konder açık ka lım ça lış ma mız da cer ra hi ile sağ lan dı ancak Mad ran ve ark.…”
Section: Discussionunclassified
“…AUTOGENOUS ARTERIOVENOUS FISTULA (AVF) is the most commonly used method for delivering hemodialysis (HD) in patients with endstage renal disease (ESRD) . However, some patients with AVFs can develop local complications, resulting in dialysis dysfunction .…”
mentioning
confidence: 99%